Channel Capacity Evaluation Model Using Storm Water Management Model - Yang Ratri Savitri; Satria Damarnegara; Mahendra Andiek Maulana; Umboro Lasminto; Novi Andriany Teguh; Nastasia Festy Margini (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2024)
Floods commonly occur in big cities with huge population densities. The increasing population number can cause a decrease in open land and green open space areas. It increases the surface runoff and induces inundation due to inadequate channel capacity. Therefore, a better design is required to minimize the inundation depth and area. This research aims to evaluate the drainage capacity of the channel dimension based on the flood discharge obtained from the rational method. The cross-section capacity was evaluated using the Storm Water Management Model by considering two types of rainfall distribution. The simulation result shows that the rainfall distribution influences the channel capacity. The flood discharge based on the Sri Harto distribution has a lower peak discharge than the Tadashi Tanimoto distribution. The result shows the significant effect of rainfall distribution types on the water depth. Therefore, it is necessary to determine the rainfall distribution method that represents the watershed characteristics used to design the drainage system.